The trends in usage and barriers of innovation management techniques in new product development - Leber, Marjan (Strojniški vestnik, 2014)
This paper reports the results of a survey on the use of innovation management techniques (IMTs) with the potential to improve effectiveness of new product development (NPD), and customer satisfaction as well as about those barriers preventing their introduction in Slovene firms in the period from 2003 to 2011. The results show that small percentage of Slovene firms used IMTs. Failure mode and effects analysis (FMEA) was found as the most applied IMT in Slovene firms with the highest perceived utility potential to reduce development costs and improve customer satisfaction. Results also indicate a trend towards the increasing use of fault tree analysis (FTA), value analysis, target costing, and TRIZ especially during the period of 2008 to 2011 which coincides with the period of economic and financial crisis. IMT complexity, a needed coaching and training and the lack of input data for IMT usage were recognized as the main barriers to implementing IMTs in Slovene firms
Keywords: longitudinalne raziskave; metode inovacijskega menedžmenta; razvoj novih izdelkov